Optimization of bioethanol production from empty fruit bunches by co-culture of saccharomyces cerevisae and aspergillus niger using statistical experimental design - Alam, Md Zahangir; Zainan, Nur Hidayah; Al-Khatib, Ma'an Fahmi Rashid (Journal of Pure and Applied Microbiology, 2014)
Production of bioethanol from oil palm empty fruit bunches (EFB) by Saccharomyces cerevisae and Aspergillus niger is among the ways of reducing environmental pollution and consumption of crude oil. This study used sequential optimization approach based on statistical experimental design including Plackett-Burman (PB) design, one-factor-at-a-time (OFAT) and face-centered central composite design (FCCCD). Among the parameters tested, pH, temperature, inoculum size, potassium dihydrogen phosphate (KH2PO4), magnesium sulphate heptahydrate (MgSO4.7H2O) and peptone showed positive effects while yeast extract, malt extract, potassium chloride, urea and agitation were influencing the production negatively. The three parameters chosen for determination of the optimum values by response surface methodology (RSM) based on the FCCCD were pH, KH2PO4 and agitation. Although agitation showed negative effects it was considered in FCCCD due to the mixing effect of fermnetation. The validity of the model was verified and the optimum value of pH 5.5, agitation of 150rpm and 0.3% of KH2PO4 led to a maximum bioethanol production of 7.4 g/l. The yield of bioethanol was determined based on the reducing sugar (16.85 g/l) obtained from the EFB.